Composición florística, estructura y biomasa de los bosques de pino-encino en la reserva Santa Rosa, Tisey, Estelí, Nicaragua - Siles, Pablo; Talavera A., Patricia; Andino Rugama, Flavia; Alaniz, Lester; Ortíz González, William (Universidad de Costa Rica, 2017)
The pine-oak forest is distributed from Central Mexico to the North of Nicaragua and represent an important ecosystem for conservation in Mesoamerica. In Nicaragua, several protected areas were established for the preservation of this ecosystem, such as the natural reserve Tisey-Estanzuela; however, this forest is considered susceptible to degradation, due to increasing deforestation and agricultural activities, besides being a narrow ecological niche (700 to 1 500 masl). We studied the floristic composition, forest structure and biomass along an altitude gradient dominated by Pinus-Quercus in forest stands on the highlands of Esteli, Northern Nicaragua. A vegetation survey on 15 plots (0.1 ha = 20x50 m) was carried out to identify patterns of tree density and diversity, and carbon stocks. In each plot, all the woody stems with diameter greater or equal to 2.5 cm were identified to species and the diameter at breast height and total height were measured. A total amount of 1 081 individuals of 24 species (17 families and 21 genera) were registered, being Q. sapotifolia, P. maximinoi, C. vicentina, M. coriacea and S. gladulosum the most abundant species representing 92 % of the individuals. Three forest associations were defined based on the abundance and dominance of Q. sapotifolia, P. maximinoi and the other species, two of those associations were dominated by Pinus (pine forest and pine-oak forest) at altitudes between 1 300 to 1 400 masl, while the third association, dominated by oak and other species (Cletha vicentina, Myrsine coriaceae and Sapium glandulosum), was found mainly at altitudes higher than 1 400 masl. Tree composition and species richness was influenced significantly by the dominance of Pinus, showing a negative correlation between the dominance and species richness of broadleaved trees other than Quercus spp. with the dominance of Pinus spp. (P < 0.001). However, the association dominated by Pinus, presented higher stem volume and biomass compared with other associations. The results from this study suggest that stands with both, an oak- or oak-pine-dominated canopy, presented the highest diversity, while Pinus dominated stands presented lower tree diversity, but higher aerial biomass and carbon storage. For this reason, we suggest that the strategies for ecosystem service payments as carbon sequestration or biodiversity conservation, must take into account differences in the type of forest associations found in this work.